2000
DOI: 10.1046/j.1439-0450.2000.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of Monoclonal Antibodies against Bovine Leukaemia Virus using Various Crude Antigen Preparations: a Comparative Study

Abstract: A total of 59 monoclonal antibodies (mAbs) specific against the bovine leukaemia virus (BLV) using different antigen preparations was produced. The five antigen preparations for immunizing BALB/c mice were: live cells (CEL), sonicated and ultracentrifuged cells (SOC), cell lysates (LYS), semi-purified BLV (PV), and formalin-treated cells (FOR) from two cell lines permanently infected with BLV (FLK-BLV and BLV-bat2). These viral component presentations were selected to obtain mAbs against specific BLV proteins:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…2) verified the specificity of the mAbs against gp51, suggesting that this is the most immunogenic protein of BLV and that the isotype IgM (60%) is predominant. Our results corroborate those reported by Llames et al, 19 who showed that 66.1% of the hybridomas they produced reacted to gp51 of BLV and 42.3% were the isotype IgM, using different antigen preparations.…”
Section: Discussionsupporting
confidence: 92%
“…2) verified the specificity of the mAbs against gp51, suggesting that this is the most immunogenic protein of BLV and that the isotype IgM (60%) is predominant. Our results corroborate those reported by Llames et al, 19 who showed that 66.1% of the hybridomas they produced reacted to gp51 of BLV and 42.3% were the isotype IgM, using different antigen preparations.…”
Section: Discussionsupporting
confidence: 92%
“…Western blot analysis Western blot analysis was performed to detect BLV‐related proteins using polyclonal sera from naturally BLV‐infected animals [28] Briefly, cells were harvested and treated with lysis buffer. After centrifuging at 14 000 × g for 30 min at room temperature, the supernatant was collected and kept at − 20 °C for further use.…”
mentioning
confidence: 99%
“…After polymerization, samples were maintained at 60 °C for 1 h, stored at room temperature, and cut into 60‐nm ultrathin sections (Ultracut E, Reichert‐Jung, Leica, Lausanne, Switzerland) for further use. To localise BLV particles/proteins in infected cells, sections were incubated with one or two BLV‐specific MoAbs as recently described [28]. Hybridoma culture supernatant was used undiluted; MoAb generated from ascites fluid were diluted 1 : 50 in PBS‐Tween 20.…”
mentioning
confidence: 99%
“…Gp51 is the most immunogenic subunit of Env and induces massive expression of specific antibodies in infected animals 20 , 21 . The N-terminal region of gp51 (the first 173 aa 22 ) contains putative receptor binding domain (RBD 16 ) together with conformational epitopes namely F, G 23 and H, involved in infectivity and syncytia formation and two neutralization domains 23 28 .…”
Section: Introductionmentioning
confidence: 99%